Copper alloy coated aluminum alloy composite conductor material and preparation method and application thereof
Through the composite material of copper alloy cladding and aluminum alloy core material, the continuous casting composite process is used to achieve solid solution of alloy elements, which solves the demand for high-performance copper-aluminum composite materials in the aerospace field, and obtains materials with high tensile strength, good plasticity and high conductivity, and eliminates the high-temperature solid solution treatment step.
Patent Information
- Application Number
- CN202411395241.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The demand for high-performance copper-aluminum composite materials in the aerospace field includes tensile strength greater than 216MPa, elongation after break of more than 6%, conductivity higher than 52% IACS and density lower than 4.954g/cm3, and the prior art cannot carry out overall solid solution treatment under high temperature conditions.
The composite material of copper alloy cladding and aluminum alloy core is quickly cooled through continuous casting composite process to achieve sufficient solid solution of alloy elements, eliminating the solid solution treatment step. The chemical composition of the material includes 0.5% to 1.5% Ni and 0.23% to 0.36% Si in the copper alloy coating, 0.5% to 1.5% Fe and 0.15% to 0.5% Cu in the aluminum alloy core material.
The obtained high-performance copper alloy-clad aluminum alloy composite material has a tensile strength of 220-300MPa, an elongation after break of 7.8-11.5% and a conductivity of 52-60% IACS, which meets the weight reduction and service needs in the aerospace field, and avoids the complexity of high-temperature solution treatment.
Smart Images

Figure CN119517485A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials, and specifically relates to a copper alloy clad aluminum alloy composite conductor material and a preparation method and application thereof. Background Art
[0002] Due to the intensified contradiction between supply and demand of copper resources and the high copper price, copper has become an important strategic resource second only to oil, which has forced companies and researchers to seek new low-cost conductor materials to replace pure copper. Copper-aluminum composite materials have the characteristics of good conductivity of copper and low density and low price of aluminum, which can achieve lightweight materials and reduce costs. At present, copper-aluminum composite materials have been widely used in power transmission, electrical equipment and electronic communications.
[0003] Reducing the weight of the entire equipment by reducing the quality of parts is of great significance to the development of the aerospace industry, such as increasing the payload, increasing the flight range or range, reducing energy consumption, and protecting the environment. At present, the lightweighting of the power system is a key issue facing the weight reduction of aerospace equipment. For example, large aircraft require more than 1 ton of pure copper conductor materials; space-based radars have all-weather and all-day strategic and tactical early warning capabilities, and have the advantages of not being restricted by the curvature of the earth and not being vulnerable to attack. The weight of the pure copper conductor accounts for about one-third of the total weight of the equipment; near-space solar drones have overcome the technical bottleneck that traditional aircraft are difficult to fly permanently, and are an important strategic fulcrum for countries to compete for near-space resources in the future. In order to give full play to the advantages of flying high and staying long, the weight reduction demand of its power system is extremely urgent. The use of copper-clad aluminum composite materials to replace pure copper conductors in aerospace equipment can achieve a weight reduction of about 50%, which plays a key role in promoting the overall design, research and development and application of aerospace equipment.
[0004] However, the harsh service conditions of aerospace have put forward strict requirements on the performance of aircraft conductor materials, including higher strength, creep resistance and composite interface bonding strength. Using copper alloys and aluminum alloys to replace pure copper and pure aluminum and developing high-performance copper alloy clad aluminum alloy composite materials is a feasible way to solve the above problems. However, there are still the following key issues to be solved:
[0005] (1) According to the weight reduction and service requirements in the aerospace field, it is urgent to develop tensile strength greater than 216MPa, elongation greater than 6%, conductivity higher than 52% IACS, and density lower than 4.954g / cm 3 High performance copper-aluminum composite material.
[0006] (2) High-strength and high-conductivity copper alloys are usually strengthened by precipitation, which requires solution treatment at high temperature to dissolve the alloying elements into the copper matrix, and then aging treatment at a lower temperature to precipitate the alloying elements to form a dispersed phase, thereby improving the strength and conductivity of the copper alloy. However, the solution temperature of copper alloy is higher than the melting point of aluminum alloy, which makes it impossible to carry out overall solution treatment of copper alloy clad aluminum alloy composite materials under high temperature conditions. It is necessary to develop a clad copper alloy material and its preparation method that can avoid solution treatment. Summary of the invention
[0007] The invention discloses a copper alloy clad aluminum alloy composite conductor material and a preparation method and application thereof, so as to solve any of the above and other potential problems in the prior art.
[0008] In order to solve the above technical problems, the technical solution provided by the present invention is: a copper alloy clad aluminum alloy composite conductor material, the cladding layer of the composite material is a copper alloy, having the following chemical composition (mass percentage): 0.5% to 1.5% Ni, 0.12% to 0.36% Si, and the balance is Cu. The core material of the composite material is an aluminum alloy, having the following chemical composition (mass percentage): 0.5% to 1.5% Fe, 0.1% to 0.5% Cu, and the balance is Al. By utilizing the rapid cooling characteristics of the continuous casting composite process, the alloy elements in the copper alloy are fully dissolved into the copper matrix during the continuous casting composite process, and a relatively dissolving effect is obtained. The tensile strength is 220 to 300 MPa, the elongation after fracture is 7.8% to 11.5%, and the conductivity is 52 to 60% IACS.
[0009] Further, the copper alloy accounts for 25% to 40% of the total volume of the composite material;
[0010] Furthermore, the cladding layer is coaxially arranged with the core material;
[0011] The continuous casting composite-deformation-aging process of the high-performance copper alloy clad aluminum alloy composite conductor material as described above, step 1: prepare the copper alloy clad aluminum alloy composite bar blank by continuous casting composite method, the copper alloy liquid insulation temperature is 1200-1300℃, the aluminum alloy liquid insulation temperature is 700-800℃, and the billet drawing speed is 90-110mm / min; step 2: perform pass rolling and drawing on the copper alloy clad aluminum alloy composite bar blank at room temperature, and the deformation amount is 64% to 84%; step 3: put the deformed copper alloy clad aluminum alloy composite material into a heat treatment furnace heated to 400-450℃ for insulation for 30-120min and then air cool. The continuous casting composite process has the characteristics of rapid cooling, which will inhibit the formation of precipitation phase in the copper alloy coating layer. The coating layer copper alloy after continuous casting composite has a good solid solution effect, and the solid solution treatment can be omitted in the subsequent process flow.
[0012] The technical points of the present invention are specifically described as follows:
[0013] (1) The aluminum alloy core material contains 0.5% to 1.5% Fe. The solid solubility of Fe in aluminum is very low. When combined with Al, it forms an Al3Fe intermediate phase, which can improve the creep resistance of aluminum alloy and meet the long-term service requirements of aerospace.
[0014] (2) The copper alloy coating layer contains 0.5% to 1.5% Ni and 0.23% to 0.36% Si, and the alloy content is relatively low. Combined with the continuous casting composite process, it has the characteristics of rapid solidification. The copper alloy coating layer after continuous casting composite has a good solid solution effect, and the solid solution treatment can be omitted in the subsequent process flow, solving the problem that the composite material cannot be solid solution treated as a whole.
[0015] (3) The copper alloy coating contains 0.5-1.5% Ni and 0.23-0.36% Si, and the weight ratio of Ni to Si in the copper alloy is 4.18-4.2. During the aging process, a dispersed strengthening phase (Ni2Si phase) will precipitate in the matrix. The precipitated phase can pin dislocations and effectively hinder dislocation movement. The performance of the copper alloy is improved through the combined effect of dislocation strengthening and precipitation strengthening. At the same time, the precipitated phase is continuously precipitated from the copper alloy of the coating layer, the copper alloy of the coating layer is purified, and the conductivity of the composite wire is improved.
[0016] Beneficial effects of the present invention:
[0017] (1) Obtain composite materials with high strength, good plasticity and electrical conductivity, with a tensile strength of 220-300 MPa, an elongation after break of 7.8-11.8%, and an electrical conductivity of 52-60% IACS, which can meet the weight reduction and service requirements in the aerospace field;
[0018] (2) The desired properties can be obtained through a continuous casting composite preparation-deformation-aging process without the need for a solution treatment process, thus solving the problem that the composite material cannot be integrally dissolved under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The present invention is a flowchart of a method for preparing a copper alloy-clad aluminum alloy composite conductor material. DETAILED DESCRIPTION
[0020] The technical solution of the present invention is further described below in conjunction with embodiments.
[0021] The present invention discloses a high-performance copper alloy-clad aluminum alloy composite material. The cladding layer of the composite material is a copper alloy having the following chemical composition (mass percentage): 0.5-1.5% Ni, 0.23-0.36% Si, the balance is Cu, and the weight ratio of Ni to Si is 4.18-4.2. The core material of the composite material is an aluminum alloy having the following chemical composition (mass percentage): 0.5-1.5% Fe, 0.15-0.5% Cu, the balance is Al.
[0022] The copper alloy accounts for 25-40% of the total volume of the composite material.
[0023] The cladding layer is coaxially arranged with the core material;
[0024] The copper alloy has a good solid solution effect after the continuous casting composite process, and the solid solution treatment can be omitted in the process flow. This is because the process has the characteristics of rapid solidification, and the alloy elements are dissolved into the copper matrix during the continuous casting composite process.
[0025] The composite material has good creep resistance because the aluminum alloy contains 0.5-1.5% Fe, the solid solubility of Fe element in aluminum is very low, only 0.05% at 650°C, and Fe combines with Al to form Al3Fe intermediate phase, which can improve the creep resistance of the aluminum alloy.
[0026] After continuous casting, compounding, deformation and aging, the composite material has a tensile strength of 220-300 MPa, an elongation after fracture of 7.8-11.5% and an electrical conductivity of 52-60% IACS.
[0027] like Figure 1 As shown, the present invention also provides a method for preparing the composite material as described above, the method specifically comprising the following steps:
[0028] S1) weighing each raw material according to the designed composition ratio;
[0029] S2) placing the mixed raw materials in S1) in a continuous casting composite device in sequence, and then heating and melting to obtain a copper alloy clad aluminum alloy composite bar blank;
[0030] The continuous casting composite process parameters in S2) are as follows: the temperature of the liquid copper alloy is 1200-1300° C., the core tube length is 45 mm, the cooling water flow rate is 600 L / h, the temperature of the liquid aluminum alloy is 700-800° C., and the billet drawing speed is 90-110 mm / min;
[0031] S3) The composite rod blank obtained in S2) is subjected to pass rolling + drawing treatment to obtain a copper alloy clad aluminum alloy composite wire.
[0032] S4) subjecting the composite wire obtained in S3) to aging treatment to obtain a high-performance copper alloy clad aluminum alloy composite wire.
[0033] The aging treatment process in S4) is as follows: placing the composite wire into a heat treatment furnace, heating to 450° C., keeping the temperature for 30-120 minutes, and then air cooling.
[0034] Embodiment 1:
[0035] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0036] The copper alloy has the following chemical composition (mass percentage): 1.0% Ni, 0.23% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 1.0% Fe, 0.3% Cu, and the balance is Al. The copper alloy accounts for 36% of the total volume of the composite material.
[0037] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1300°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 700°C; and the billet drawing speed is 110mm / min.
[0038] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0039] (1) Through room temperature groove rolling and drawing, the deformation amount is 84% to obtain a composite wire;
[0040] (2) Heat to 450°C and keep at this temperature for 30 min, then air cool.
[0041] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 241 MPa, an elongation after fracture of 7.8%, and a conductivity of 54.5% IACS.
[0042] Embodiment 2:
[0043] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0044] The copper alloy has the following chemical composition (mass percentage): 1.0% Ni, 0.23% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 1.0% Fe, 0.3% Cu, and the balance is Al. The copper alloy accounts for 36% of the total volume of the composite material.
[0045] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1300°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 700°C; and the billet drawing speed is 90mm / min.
[0046] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0047] (1) Through room temperature groove rolling and drawing, the deformation amount is 84% to obtain a composite wire;
[0048] (2) Heat to 450°C and keep at this temperature for 30 min, then air cool.
[0049] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 241 MPa, an elongation after fracture of 7.8%, and a conductivity of 54.5% IACS.
[0050] Embodiment 3:
[0051] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0052] The copper alloy has the following chemical composition (mass percentage): 1.0% Ni, 0.23% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 1.0% Fe, 0.3% Cu, and the balance is Al. The copper alloy accounts for 36% of the total volume of the composite material.
[0053] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1300°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 700°C; and the billet drawing speed is 100mm / min.
[0054] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0055] (1) Through room temperature groove rolling and drawing, the deformation amount is 84% to obtain a composite wire;
[0056] (2) Heat to 450°C and keep at this temperature for 30 min, then air cool.
[0057] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 241 MPa, an elongation after fracture of 7.8%, and a conductivity of 54.5% IACS.
[0058] Embodiment 4:
[0059] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0060] The copper alloy has the following chemical composition (mass percentage): 1.0% Ni, 0.23% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 1.0% Fe, 0.3% Cu, and the balance is Al. The copper alloy accounts for 36% of the total volume of the composite material.
[0061] The composite rod blank was prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters were as follows: the temperature of the liquid copper alloy was 1250°C; the core tube length was 45mm; the cooling water flow rate was 600L / h; the temperature of the liquid aluminum alloy was 750°C; and the billet drawing speed was 110mm / min. The copper alloy accounted for 36% of the total volume of the composite material.
[0062] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0063] (1) Through room temperature groove rolling and drawing, the deformation amount is 84% to obtain a composite wire;
[0064] (2) Heat to 450°C and keep at this temperature for 60 min, then air cool.
[0065] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 255 MPa, an elongation after fracture of 11.5%, and a conductivity of 55.3% IACS.
[0066] Embodiment 5:
[0067] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0068] The copper alloy has the following chemical composition (mass percentage): 1.0% Ni, 0.23% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 1.0% Fe, 0.3% Cu, and the balance is Al. The copper alloy accounts for 36% of the total volume of the composite material.
[0069] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1250°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 750°C; and the billet drawing speed is 110mm / min.
[0070] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0071] (1) Through room temperature groove rolling and drawing, the deformation amount is 84% to obtain a composite wire;
[0072] (2) Heat to 450°C and keep at this temperature for 120 min, then air cool.
[0073] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 253 MPa, an elongation after fracture of 8.3%, and a conductivity of 56.9% IACS.
[0074] Embodiment 6:
[0075] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0076] The copper alloy has the following chemical composition (mass percentage): 1.5% Ni, 0.36% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 1.0% Fe, 0.3% Cu, and the balance is Al. The copper alloy accounts for 36% of the total volume of the composite material.
[0077] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1250°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 750°C; and the billet drawing speed is 110mm / min.
[0078] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0079] (1) Through room temperature groove rolling and drawing, the deformation amount is 84% to obtain a composite wire;
[0080] (2) Heat to 450°C and keep at this temperature for 60 min, then air cool.
[0081] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 287 MPa, an elongation after fracture of 10.5%, and a conductivity of 53.6% IACS.
[0082] Embodiment 7:
[0083] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0084] The copper alloy has the following chemical composition (mass percentage): 0.5% Ni, 0.12% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 1.5% Fe, 0.5% Cu, and the balance is Al. The copper alloy accounts for 36% of the total volume of the composite material.
[0085] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1250°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 750°C; and the billet drawing speed is 110mm / min.
[0086] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0087] (1) Through room temperature groove rolling and drawing, the deformation amount is 84% to obtain a composite wire;
[0088] (2) Heat to 450°C and keep at this temperature for 30 min, then air cool.
[0089] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 220 MPa, an elongation after fracture of 11.5%, and a conductivity of 60% IACS.
[0090] Embodiment 8:
[0091] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0092] The copper alloy has the following chemical composition (mass percentage): 1.5% Ni, 0.36% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 1.0% Fe, 0.3% Cu, and the balance is Al. The copper alloy accounts for 36% of the total volume of the composite material.
[0093] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1250°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 800°C; and the billet drawing speed is 110mm / min.
[0094] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0095] (1) Through room temperature groove rolling and drawing, the deformation amount is 84% to obtain a composite wire;
[0096] (2) Heat to 450°C and keep at this temperature for 60 min, then air cool.
[0097] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 287 MPa, an elongation after fracture of 10.5%, and a conductivity of 53.6% IACS.
[0098] Embodiment 9:
[0099] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0100] The copper alloy has the following chemical composition (mass percentage): 1.5% Ni, 0.36% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 1.0% Fe, 0.3% Cu, and the balance is Al. The copper alloy accounts for 36% of the total volume of the composite material.
[0101] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1250°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 750°C; and the billet drawing speed is 110mm / min.
[0102] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0103] (1) Through room temperature groove rolling and drawing, the deformation amount is 64% to obtain a composite wire;
[0104] (2) Heat to 450°C and keep at this temperature for 60 min, then air cool.
[0105] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 277 MPa, an elongation after fracture of 10.5%, and a conductivity of 53.6% IACS.
[0106] Embodiment 10:
[0107] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0108] The copper alloy has the following chemical composition (mass percentage): 1.5% Ni, 0.36% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 1.0% Fe, 0.3% Cu, and the balance is Al. The copper alloy accounts for 36% of the total volume of the composite material.
[0109] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1250°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 750°C; and the billet drawing speed is 110mm / min.
[0110] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0111] (1) by room temperature groove rolling and drawing, the deformation amount is 70%, and the composite wire is obtained;
[0112] (2) Heat to 450°C and keep at this temperature for 60 min, then air cool.
[0113] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 280 MPa, an elongation after fracture of 10.5%, and a conductivity of 53.6% IACS.
[0114] Embodiment 11:
[0115] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0116] The copper alloy has the following chemical composition (mass percentage): 1.5% Ni, 0.36% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 1.0% Fe, 0.3% Cu, and the balance is Al. The copper alloy accounts for 25% of the total volume of the composite material.
[0117] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1250°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 750°C; and the billet drawing speed is 110mm / min.
[0118] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0119] (1) by room temperature groove rolling and drawing, the deformation amount is 70%, and the composite wire is obtained;
[0120] (2) Heat to 450°C and keep at this temperature for 60 min, then air cool.
[0121] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 231 MPa, an elongation after fracture of 10.5%, and a conductivity of 55.2% IACS.
[0122] Embodiment 12:
[0123] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0124] The copper alloy has the following chemical composition (mass percentage): 1.5% Ni, 0.36% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 1.0% Fe, 0.3% Cu, and the balance is Al. The copper alloy accounts for 40% of the total volume of the composite material.
[0125] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1250°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 750°C; and the billet drawing speed is 110mm / min.
[0126] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0127] (1) by room temperature groove rolling and drawing, the deformation amount is 70%, and the composite wire is obtained;
[0128] (2) Heat to 450°C and keep at this temperature for 60 min, then air cool.
[0129] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 300 MPa, an elongation after fracture of 10.5%, and a conductivity of 52.9% IACS.
[0130] Embodiment 13:
[0131] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0132] The copper alloy has the following chemical composition (mass percentage): 1.5% Ni, 0.36% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 1.0% Fe, 0.3% Cu, and the balance is Al. The copper alloy accounts for 36% of the total volume of the composite material.
[0133] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1250°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 750°C; and the billet drawing speed is 110mm / min.
[0134] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0135] (1) by room temperature groove rolling and drawing, the deformation amount is 70%, and the composite wire is obtained;
[0136] (2) Heat to 400℃ and keep at this temperature for 90 min, then air cool.
[0137] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 261 MPa, an elongation after fracture of 7.5%, and a conductivity of 52.1% IAC.
[0138] Embodiment 14:
[0139] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0140] The copper alloy has the following chemical composition (mass percentage): 1.5% Ni, 0.36% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 0.5% Fe, 0.1% Cu, and the balance is Al. The copper alloy accounts for 36% of the total volume of the composite material.
[0141] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1250°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 750°C; and the billet drawing speed is 110mm / min.
[0142] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0143] (1) by room temperature groove rolling and drawing, the deformation amount is 70%, and the composite wire is obtained;
[0144] (2) Heat to 450°C and keep at this temperature for 60 min, then air cool.
[0145] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 251 MPa, an elongation after fracture of 10.5%, and a conductivity of 53.9% IAC.
[0146] Embodiment 15:
[0147] A method for preparing a copper alloy-clad aluminum alloy composite conductor material, the preparation method specifically comprising the following steps:
[0148] The copper alloy has the following chemical composition (mass percentage): 1.5% Ni, 0.36% Si, and the balance is Cu. The aluminum alloy has the following chemical composition (mass percentage): 0.7% Fe, 0.15% Cu, and the balance is Al. The copper alloy accounts for 36% of the total volume of the composite material.
[0149] The composite rod blank is prepared by the continuous casting composite process in patent CN201610496178.9, and the process parameters are as follows: the temperature of the liquid copper alloy is 1250°C; the core tube length is 45mm; the cooling water flow rate is 600L / h; the temperature of the liquid aluminum alloy is 750°C; and the billet drawing speed is 110mm / min.
[0150] The above super composite bar blank is subjected to cold rolling, drawing and aging treatment, and the process is as follows:
[0151] (1) by room temperature groove rolling and drawing, the deformation amount is 70%, and the composite wire is obtained;
[0152] (2) Heat to 450°C and keep at this temperature for 60 min, then air cool.
[0153] The obtained copper alloy clad aluminum alloy composite wire has a tensile strength of 255 MPa, an elongation after fracture of 10.5%, and a conductivity of 52.5% IAC.
[0154] The above is a detailed introduction to a copper alloy clad aluminum alloy composite conductor material and its preparation method and application provided in the embodiment of the present application. The description of the above embodiment is only used to help understand the method and its core idea of the present application; at the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present application.
[0155] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different nouns to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. As mentioned throughout the specification and claims, "including" and "comprising" are open-ended terms, so they should be interpreted as "including / including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problem within a certain error range and basically achieve the technical effect. The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application, and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the attached claims.
[0156] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.
[0157] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0158] The above description shows and describes several preferred embodiments of the present application, but as mentioned above, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present application, and should be within the scope of protection of the claims attached to the present application.
Claims
1. A copper alloy clad aluminum alloy composite conductor material, characterized in that: The composite conductor material is a copper-clad aluminum concentric bimetallic composite structure, the cladding layer is a copper alloy, the core is an aluminum alloy, and the volume fraction of the copper alloy in the composite wire is 25% to 40%; Wherein: the mass percentage of the chemical composition of the copper alloy is: 0.5% to 1.5% Ni, 0.12% to 0.36% Si, and the balance is Cu; The mass percentage of the chemical composition of the aluminum alloy is: 0.5% to 1.5% Fe, 0.1% to 0.5% Cu, and the balance is Al.
2. The composite conductor material according to claim 1, characterized in that: The core has an Al3Fe intermediate phase.
3. The composite conductor material according to claim 1, characterized in that: The weight ratio of Ni to Si in the copper alloy is 4.18-4.2, and the copper alloy has precipitation.
4. A method for preparing the composite conductor material according to any one of claims 1 to 3, characterized in that: The method specifically comprises the following steps: S1) according to the designed proportion, weigh the raw materials of copper alloy and aluminum alloy respectively for use; S2) mixing the raw materials weighed in S1) according to a certain ratio, placing the mixed raw materials in a continuous casting composite device in turn, and then heating and melting to obtain a copper alloy clad aluminum alloy composite bar blank; S3) subjecting the copper alloy clad aluminum alloy composite rod blank obtained in S2) to pass rolling + drawing treatment to obtain a copper alloy clad aluminum alloy composite wire; S4) subjecting the copper alloy clad aluminum alloy composite wire obtained in S3) to aging treatment to obtain a final product.
5. The method according to claim 4, characterized in that The ratio in S2) is: the volume fraction of the copper alloy in the composite wire is 25% to 40%; The continuous casting composite process parameters in S2) are as follows: the temperature of the liquid copper alloy is 1200-1300°C, the cooling water flow rate is 600L / h, the temperature of the liquid aluminum alloy is 700-800°C, and the billet drawing speed is 90-110mm / min.
6. The method according to claim 4, characterized in that The deformation amount in S3) is 64% to 84%.
7. The method according to claim 4, characterized in that The aging treatment process in S4) is as follows: the aging treatment temperature is 400-450° C., the heat preservation time is 30-120 minutes, and then air cooling is performed.
8. The method according to claim 4, characterized in that The composite conductor material prepared by the method has a tensile strength of 220-300 MPa, an elongation after fracture of 7.8-11.8%, and an electrical conductivity of 52-60% IACS.
9. A composite conductor material prepared by the method according to any one of claims 4 to 8, which is used for preparing conductor wires in the aerospace field.
Citation Information
Patent Citations
A high-efficiency continuous casting equipment and process for copper-clad aluminum composite materials
CN106111922B
Aluminum alloy conductor material with high compressive creep resistance and low resistivity and preparation method thereof, and cable
CN104928537A
Copper alloy and aluminum alloy composite wire and preparation processing method thereof
CN105779828A
Efficient continuous casting forming equipment and process for copper-clad aluminum composite
CN106111922A
Copper-clad aluminum alloy composite conductor for aerospace cable and processing technology thereof
CN110828025A